Catalysts for Collective Conscientization in Environmental Adult Education: Mr. Floatie, Tree Squatting and Save-our-Surfers - Pierre Walter (Adult Education Research Conference, 2007)
This study examines how cultural codes in environmental adult education can be used to “frame” collective identity, develop counter-hegemonic ideologies, and catalyze “educative-activism” within social movements. Three diverse examples are discussed, spanning movements in urban Victoria, BC, the redwoods of northern California and the coral reefs and beaches of Hawai’i.